2015
DOI: 10.1089/jmf.2013.0170
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Antilipidemic Effects of Manilkara zapota

Abstract: Manilkara zapota is a tropical evergreen tree belonging to the Sapotaceae family; its parts are used in alternative medicine to treat coughs and colds and possess diuretic, antidiarrheal, antibiotic, antihyperglycemic, and hypocholesterolemic effects. There are no studies on metabolic profile after using the fruit, and this study aimed at evaluating the effects of the leaf and pulp of M. zapota fruit on the metabolic profile of Wistar rats. Male rats were treated for 50 days with M. zapota leaf juice or fruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 41 publications
0
25
0
2
Order By: Relevance
“…The fruits are popular in tropical countries and the leaves are used for antidiabetic treatment. Various antidiabetic and antilipidemic effects of M. zapota fruits have been reported [11]. In addition, the traditional uses, phytochemistry and pharmacological activity of the plant have been reviewed [12].…”
Section: Introductionmentioning
confidence: 99%
“…The fruits are popular in tropical countries and the leaves are used for antidiabetic treatment. Various antidiabetic and antilipidemic effects of M. zapota fruits have been reported [11]. In addition, the traditional uses, phytochemistry and pharmacological activity of the plant have been reviewed [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fagbohun & Odufuwa (84) observed that the leaves of the cashew tree (Anarcadium occidentale L.) demonstrated hypoglycemic activity in rats induced to diabetes by streptozotocin. And the leaves of the sapodilla (Manilkara zapota) also demonstrated cardioprotective effects by reducing the levels of glucose, insulin, leptin, cholesterol and triglycerides in Wistar rats (85) .…”
Section: Studies Performed With Fig (Ficus Caricamentioning
confidence: 99%
“…A decoction of the leaves of M. zapota is used as an antipyretic, for treatment of hemorrhage, wounds, and ulcers; other uses include a remedy for diarrhea, intestinal inflammation, lack of appetite, and normalization of blood pressure [9]. Some pharmacological studies have confirmed specific medicinal properties of the leaves such as antidiabetic, antilipidemic, hypoglycemic, and antioxidant activity [10,11,12,13]. While the phytochemistry of the fruit has been explored, reporting the presence of bioactive and novel polyphenols [14], the leaves have only had qualitative studies suggesting the presence of phenols and flavonoids [10] and a single phytochemical study reporting the isolation of lupeol acetate, oleanolic acid, apigenin-7-O-α- l -rhamnoside, myricetin-3-O-α- l -rhamnoside, and caffeic acid [15].…”
Section: Introductionmentioning
confidence: 99%